Value Adding in Mon Ethnic Food of Mon Ban Sao Kradong Community, Phra Nakhon Si Ayutthaya Province - Liaotrakoon, Wijitra; Liaotrakoon, Vachiraya; Wongsaengtham, Wanpa; Suwannaphan, Sunisa; Thongrak, Phakhwan; Duamkhanmanee, Raweewon; Phoondee, Yupin (Area Based Development Research Journal, 2020)
The research aims to add value to chulta and roselle, the two local plants with sour taste and mucilage, commonly used as ingredients of Mon ethnic food. The participatory action research was performed with the participation of 32 people from Mon Ban Sao Kradong community, Bang Pa-in district, Phra Nakhon Si Ayutthaya province. The research process is divided into 3 phases. Firstly, the community’s local plants product development is conducted by trying out the recipe, studying production process, checking product quality, food condition during storage, and cost estimation. Secondly, research data is shared with community and knowledge is transferred to community members. Thirdly, market testing is performed with general consumers and tourists. A unique product of the community is honey-flavoured chulta juice, which has been accepted for its appearance, color, odor, taste, texture, and its antioxidatant property and phenolic content. Raman teas, which consist of chulta tea, roselle leaf tea, roselle flower tea, and Pikul flower tea with antioxidative activity are also well accepted. These products can be stored for over 3 months at room temperature. The research project has raised the community awareness of local Mon ethnic plants’ value and importance. The chulta and roselle planted have been grown more broadly in order to serve as raw materials for value-added products. Finally, a local group established for producing and distributing these products leads to local employability and income of over 8,000 baht/month, as well as community tourism promotion.